ASSOCIATION OF MATERNAL BMI AND ANTHROPOMETRY OF NEW-BORN: A HOSPITAL-BASED CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Higher newborn morbidity and death are associated with low birth weight, which remains a significant public health issue in poor nations. Foetal growth and newborn anthropometric outcomes are significantly influenced by the nutritional state of the mother, particularly BMI (Body Mass Index). The purpose of this study was to evaluate the relationship between the newborn's anthropometry and the mother's BMI. Methods: A hospital-based cross-sectional study was conducted among 700 full-term pregnant women admitted for delivery at Dr. Prabhakar Kore Charitable Hospital, Belagavi, from January to December 2017. Women with singleton live births were included, while mothers with medical disorders and babies with congenital anomalies were excluded. Maternal anthropometric parameters, including height, weight, and BMI during all trimesters were recorded. Within an hour of birth, newborn anthropometric measurements were taken, including birth weight, length, head circumference, and chest circumference. SPSS version 16.0 was used to analyse the data, and associations were found using the chi-square test and ANOVA. Results: The mean birth weight of the newborns was 2.82±0.4 kg, and the frequency of LBW was 17.43%. The newborn's birth weight was significantly positively correlated with the mother's BMI throughout all three trimesters (p